Computational simulation of incineration of chemically and biologically contaminated wastes. (3rd April 2021) - Lemieux, Paul; Boe, Timothy; Tschursin, Anna; Denison, Martin K.; Davis, Kevin; Swensen, Dave
ABSTRACT: This paper describes the modeling approach and example results for a newly introduced computational simulation tool to evaluate waste destruction in thermal incineration systems. The Configured Fireside Simulator (CFS) is a software simulator, originally developed for the Department of Defense to evaluate operations of the chemical demilitarization incinerators processing the chemical warfare agent stockpile of the US. The software was later adapted for use by the U.S. Environmental Protection Agency (EPA) to provide for the ability to run "what if" scenarios of waste streams contaminated with chemical/biological (CB) threat agents in four specific incinerators, including the EPA's pilot-scale Rotary Kiln Incinerator Simulator (RKIS) facility, as well as three commercial incinerators based on design criteria for actual operating facilities. These commercial incinerators include a Medical/Pathological Waste Incinerator, a Hazardous Waste Burning Rotary Kiln, and a Waste-to-Energy Stoker-type combustor. The CFS uses three-dimensional computational fluid dynamics coupled with detailed chemical kinetic data for destruction of chemical warfare agents, coupled with kinetic data for biological agent destruction derived from bench- and pilot-scale experiments to predict the way agent-containing materials will behave under full-scale combustion conditions in several different incinerator types. The objective of this paper is to describe the CFS software, how it works, and potential applications of this software to real-world situations. This software could be a valuable tool for researchers, regulators, and industry to evaluate potential operating conditions to help guide testing activities and develop operational scenarios for difficult-to-manage waste streams. Although this software has been under development for several years, this paper represents the software's first introduction to the scientific community in the peer-reviewed literature. Implications: Adapting the Configured Fireside Simulator that was originally developed for the Department of Defense to evaluate operations of the chemical demilitarization incinerators processing the chemical warfare agent stockpile of the US to provide for the ability to run "what if" scenarios on civilian waste streams contaminated with CB agents is a useful tool for national preparedness. Such a model could be used in planning and response efforts to provide a better understanding of incineration capacity, development of feed strategies, and assessment of throughput limitations for CB incidents as well as other difficult-to-test waste streams and contaminants.